Assistance Efforts and Recognition of Students’ Body Posture Post Pandemi Covid -19 at SMA Negeri 85 West Jakarta - Amir, Trisia Lusiana; Munawwarah, Muthiah; Lesmana, Syahmirza Indra; Abdurrasyid, Abdurrasyid (Poltekkes Kemenkes Denpasar, 2023)
The process of learning from home during the Covid-19 pandemic, which is generally sedentary, causes changes in the basic functions of the body. In addition, lack of knowledge about movement and basic body functions and minimal checking of student body posture at school can have an impact on decreasing student fitness, concentration, and achievement. This can be seen when students began to be active again to carry out 100% learning from schools after the Covid-19 pandemic. The purposes of this community service activity are to provide preventive and curative efforts through educational assistance and examination of movements and basic body functions to increase student insigh about ideal body posture. This activity was carried out at SMA Negeri 85 West Jakarta with a target of 35 students, through four main activities: (1) preparation and production of educational materials about movements and basic body functions, (2) mentoring and delivery of material to the students, (3) examine movements and basic body functions, and (4) evaluate. The results achieved during the implementation showed the seriousness and enthusiasm of the students and based on the results of the examination, there were still students who had abnormal BMI and abdominal circumference. Likewise for body posture, examination of the upper extremities with a neck shoulder line test and examination of the lower extremities with true length and appearance length tests found dissimilarities between the right and left sides of the body. Furthermore, in the examination of body functions through isometric and prone plank tests, there are scores below the normal score, which means that there is a decrease in basic body functions like muscle strength and endurance. The results of this examination are evaluated and students will be able to recognize their body posture and take actions/steps that can maintain/ improve the posture to be better.